Key developments in the cancer neuroscience field - Monje, Michelle; Winkler, Frank (Nature cancer, 2025)
Over the past decade, multiple lines of inquiry have converged on the appreciation that the nervous system plays crucial roles in cancer pathophysiology. Key conceptual advances will mark 2025 as a milestone year in which the ‘emerging’ cancer neuroscience field developed into an established field. Here, we discuss the latest developments.
Online veröffentlicht: 10. Dezember 2025
Gesehen am 26.02.2026